Comparing the systematic risk of developing and developed countries in East Asia: Empirical evidence from 1997 Asian Financial Crisis - Choi, Hei Ting (2017)
The global market is becoming increasingly integrated nowadays. Risk becomes a hot topic in regard to markets for researchers. In the view of macroeconomics, countries and institutions highly focus on systematic risk to the degree of being involved into a financial crisis when other financial systems collapse. This paper aims to assess the Asian Financial Crisis that happened in 1997 to 1998, to understand the systematic risk in both developed and developing countries. The purpose of this study is to find out which group was less impacted by systematic risk during the crisis, by understanding how the major two indicators, performance and interconnectedness, would response to systematic risk. Thus, the government can set risk policies to minimize impact of systematic risk with reference to the better performed and less interconnected group as a direction for future stability and consideration.